Macroprudential policy in Asian economies - Soyoung Kim (Asian Development Bank (ADB), 2019)
This paper analyzes the conduct and effects of macroprudential policy in 11 Asian economies. Of these, India, the People's Republic of China, and the Republic of Korea frequently used loan-to-value ratios and required reserve ratios even before the global financial crisis. India and the People's Republic of China are the most frequent users of macroprudential policy tools. Since 2000, tightening actions have been more frequent than loosening in the 11 economies. Most took tightening actions more frequently after the global financial crisis than before it. In most of these economies, macroprudential policy tends to be tightened when credit expands. The main empirical results from the analysis, which uses panel vector autoregression models, are that contractionary macroprudential policy has significant negative effects on credit and output; and that these effects are qualitatively similar to those of monetary policy. This suggests that policy authorities may experience potential policy conflicts when credit conditions are excessive and the economy is in recession.
Keywords: E58; E60; G28; 330; credit; macroprudential policy; monetary policy; output; vector autoregression